Legitimasi Tuan Guru di Tengah Pandemi Virus Corona ditinjau Dari Teori Orientasi, Sikap, dan Perilaku Keagamaan - Sukardiman (Kopertais Wilayah III Yogyakarta, 2021)
Indonesia is a country that is based on God Almighty, in accordance with article 29 paragraph 1, so religious leader are needed in socializing or preaching about divinity, including the social value of God’s teachings. In Lombok a religious figure is called Tuan Guru which is the title of a Kyai who specialize in the culture of the Sasak people, as well as an effort to increase community participation in national development through religious language. The status of Tuan Guru is obtained because of his expertise in the field of religion, moral integrity, ability to teach, and preach. Tuan Guru is also considered to have blessing, so it’s no wonder the people are willing to flock to get blessings. Tuan Guru not only has legitimacy with his religious language, but also charismatic legitimacy. Tuan Guru is a figure who has charisma, very trusted and a role model for the Sasak people, and has a strong social control function in the mindst of the corona virus pandemic and helps people maintain their values of community solidarity in stopping the spread of the corona virus. Charismatic legitimacy is an important social capital in the midst of a pandemic, so that the religious orientation of the community becomes intrinsic, meaning that it is not selfish, but has an open attitude in acceting fatwas and appeals from the Indonesian Ulama’ council and the government, so that the religious attitudes and behavior orf each individual will be reflects compliance. Without charisma, being able to make the language of religion not reach the community, bot must go hand in hand. Finally, Tuan Guru must explain to the public about the dimensions of religion, not only the ritual, sacred, theological dimensions, but also the profane dimension, namely worldliness that needs to be of common concern, one of which is the problem of the corona virus pandemic which is a human problem. Keyword: Tuan Guru, Virus Corona, religious orientation, attitudes, and behavior.